Temperature characteristics of Gate all around nanowire channel Si-TFET - Agha, Firas Natheer Abdul-kadir; Hashim, Yasir; Jabbar, Waheb A. (IOP Publishing, 2021)
This paper study the impact of working temperature on the electrical characteristics of gate all around nanowire channel Si-TFET and examines the effect of working temperature on threshold voltage, transcondactance (gm), ION/IOFF ratio, drain induced barrier lowering (DIBL), and sub-threshold swing (SS). The (Silvaco) simulation tool has been used to investigate the working temperature on the Si-TFET characteristics. The temperature range in this study is from -25 to 150°C. The results indicate that the TFET must work in electronic circuits with the lower temperature as possible to get better performances. Furthermore, the TFET has good performances as a temperature nanosensor with diode connection mode under ON conditions.